Mast Cell and Innate Immune Cell Communication in Cholestatic Liver Disease - Bernard, Jessica K.; Marakovits, Corinn; Smith, Leah G.; Francis, Heather (Seminars in Liver Disease, 2023)
Mast cells (MCs) contribute to the pathogenesis of cholestatic liver diseases (primary sclerosing cholangitis [PSC] and primary biliary cholangitis [PBC]). PSC and PBC are immune-mediated, chronic inflammatory diseases, characterized by bile duct inflammation and stricturing, advancing to hepatobiliary cirrhosis. MCs are tissue resident immune cells that may promote hepatic injury, inflammation, and fibrosis formation by either direct or indirect interactions with other innate immune cells (neutrophils, macrophages/Kupffer cells, dendritic cells, natural killer, and innate lymphoid cells). The activation of these innate immune cells, usually through the degranulation of MCs, promotes antigen uptake and presentation to adaptive immune cells, exacerbating liver injury. In conclusion, dysregulation of MC-innate immune cell communications during liver injury and inflammation can lead to chronic liver injury and cancer.
Keywords: mast cells; cholestasis; innate immune cells